Cultural differences in the understanding of modelling and feedback as sources of self‐efficacy information. (21st September 2015) - Ahn, Hyun Seon; Usher, Ellen L.; Butz, Amanda; Bong, Mimi
Abstract : Background: The potential role of culture in the development and operation of self‐efficacy has been acknowledged by researchers. Clearer understanding of this cultural impact will benefit from research that shows how the same efficacy information is evaluated across cultures. Aims: We tested whether two sources of self‐efficacy information delivered by multiple social agents (i.e., vicarious experience and social persuasion) were weighed differently by adolescents in different cultures. Sample: Of 2, 893 middle school students in Korea ( n  =   416), the Philippines ( n  =   522), and the United States ( n  =   1, 955) who completed the survey, 400 students were randomly pooled from each country. Methods: Invariance of the measurement and of the latent means for self‐efficacy and self‐efficacy sources across the groups was tested by multigroup confirmatory factor analysis. Predictive utility of the self‐efficacy sources was compared by multigroup structural equation modelling. Results: Compared to the students in the two collectivistic countries, the US students reported significantly higher mathematics self‐efficacy. Whereas the efficacy beliefs of the Korean and the US students were predicted equally well by the vicarious experience from their teachers and the social persuasion by their family and peers, those of the Filipino adolescents were best predicted by the social persuasion from their peers. Conclusions: This study provided empirical evidence that socially conveyed sources of self‐efficacy information are construed and evaluated differently across cultures, depending on who delivered the efficacy‐relevant information.